A mortality study of the last outbreak of yellow fever in Barcelona City (Spain) in 1870 Estudio de la mortalidad del último brote de fiebre amarilla en la ciudad de Barcelona (España) en 1870 - Jaume Canela Soler; Maria Rosa Pallarés Fusté; Rafael Abós Herràndiz; Carme Nebot Adell; Robert S. Lawrence (Elsevier, 2009)
Background: The last outbreak of yellow fever in the city of Barcelona, Spain, was caused by a ship arriving from Cuba. The objective of this study was to describe and analyze the epidemic of 1870 by using the available mortality data. Methods: The information on 1,235 deaths identified in the parochial registries was analyzed, using statistical and epidemiological procedures for epidemic outbreaks. Results: Mortality due to yellow fever was 549.7 per 100,000 inhabitants. The temporal distribution of the deaths showed two peaks at the end of September and October with the last fatalities occurring in December 1870. The distribution of the fatalities in the city's neighborhoods was unequal. In La Barceloneta, in particular, more fatalities were found in the streets adjacent to the port than in the most remote streets (r=0.83; p<0.0001). Conclusions: This study reveals a temporal bimodal mortality distribution for yellow fever during the outbreak, with a high impact in adult men and in the La Barceloneta neighborhood. Objetivo: El último brote de fiebre amarilla en la ciudad de Barcelona, España, se originó a partir de un barco que venía de Cuba. El objetivo de este estudio es describir y analizar esa epidemia ocurrida en 1870, utilizando los datos disponibles de mortalidad. Métodos: La información de las 1235 defunciones identificadas en los registros parroquiales se ha analizado utilizando los procedimientos estadísticos y epidemiológicos para brotes epidémicos. Resultados: La tasa de mortalidad por fiebre amarilla fue de 549.7 por 100,000 habitantes. La distribución temporal de las muertes tenía dos modas en el final de septiembre y octubre, y los últimos muertos ocurrieron en diciembre de 1870. La distribución de las defunciones según los barrios de la ciudad fue desigual. En La Barceloneta, en particular, hubo mas muertos en las calles adyacentes al puerto que en las más lejanas (r=0,83; p<0,0001). Conclusiones: Este estudio muestra una distribución bimodal de la mortalidad por fiebre amarilla durante el brote, con un impacto alto en hombres adultos, y en el barrio de La Barceloneta.